Satisfactory outcomes following a second autologous hematopoietic cell transplantation for multiple myeloma in poor stem cell mobilizers: a retrospective study on behalf of the Chronic Malignancies Working Party of the EBMT - Sever, Matjaz; Drozd-Sokolowska, Joanna; Gras, Luuk; Koster, Linda; Folber, Frantisek; Mielke, Stephan; Fenk, Roland; Basak, Grzegorz W.; Apperley, Jane F.; Byrne, Jennifer; Rambaldi, Alessandro; Ringhoffer, Mark; et al. (Bone marrow transplantation, 2025)
Autologous hematopoietic cell transplants (auto-HCTs) remain the standard of care for transplant-eligible MM patients. The general practice has been to undergo upfront apheresis following induction to collect sufficient number of CD34+ cells to facilitate two auto-HCTs. However, 5-30% of MM patients do not initially mobilise a sufficient number of hematopoietic stem cells and are classified as poor mobilizers (PM). We compared the baseline characteristics and outcomes of 61 PMs and 816 non-PM patients who underwent a second auto-HCT and who were enrolled in the non-interventional CALM study (NCT01362972). Only patients who collected CD34+ prior to auto-HCT1 were included. Auto-HCT2 comprised both tandem and salvage transplants. PMs were re-mobilized with plerixafor (n = 24, 39.3%) or non-plerixafor-based regimens (n = 37, 60.7%). There were no significant differences in engraftment, progression-free survival (PFS) or overall survival (OS) after the second auto-HCT between PM and non-PM patients. There was a trend to shorter PFS in PM patients undergoing salvage auto-HCT (median 9.6 vs. 12.9 months; p = 0.08) but no significant difference in OS. The median OS was 41.1 months for PM and 41.2 months for non-PM patients (p = 0.86). These data suggest that salvage mobilization is effective and does not affect overall outcomes after a second auto-HCT.
Online veröffentlicht: 12. November 2024
Gesehen am 10.09.2025